Natural born opportunists. Issue 8 (18th September 2017) - Fennimore, Anne
Abstract : Purpose: The purpose of this paper is to adapt research conducted on subclinical psychopaths and Machiavellians to conceptualise false agents in transaction cost economics (TCE). Both opportunism and information asymmetry provide a means to manipulate contractual relationships, pursuing existing loopholes for self-interest, while uncertainty and small-numbers bargaining allow false agents to exploit existing agreements during periods of rapid change, growth, and development. Considering differences in contract length preference may inform our understanding of subclinical psychopaths and Machiavellians. Contextually, the rise of "quasi-governmental" hybrid organisations may produce an ideal prospect for "natural born" opportunists to reap self-interested benefits through contractual loopholes. Design/methodology/approach: This theoretical paper addresses social norms and blind trust in contractual relationships. In turn, blind trust may provide clues about the environmental conditions that facilitate manipulation by subclinical psychopaths and Machiavellians during negotiations of contract term length. Findings: Williamson's (1975) TCE framework provides a novel approach to subclinical psychopathic and Machiavellian behaviour by agents. Assumptions about behavioural norms may differ between the contracting party and the agent, leading to positive behavioural expectations of trust such as confidence, reciprocity, and history. The length of the contractual relationship may distinguish subclinical psychopaths from Machiavellians. The subclinical psychopath is more likely to behave opportunistically in short-term contracts, while Machiavellians more likely amass goodwill to behave opportunistically in long-term contracts. The role of uncertainty, small-numbers bargaining, information asymmetry, and opportunism is particularly relevant in quasi-governmental organisations when agents are "natural born" opportunists. Originality/value: This theoretical paper adds to discussion of TCE related problems in organisations. "Natural born" opportunistic agents are more likely to take advantage of principals who extend trust as a goodwill gesture in a contractual relationship. Trust often represents a mental shortcut, based on "gut" reactions to save time, especially in dynamic environments. Hybrid organisations represent one such environment, in which contracting of goods and services renders comprehensive monitoring impracticable. Yet, scholarship adheres to legal mechanisms as safeguards against opportunism without acknowledging social norms that guide blind trust. Finally, contrasting motives between principals and false agents creates an inherent relationship asymmetry.